Association between ambulatory status and call bell use in hospitalized patients—A retrospective cohort study. (13th November 2019) - Capo‐Lugo, Carmen E.; Shumock, Kara; Young, Daniel L.; Klein, Lisa; Cassell, Andre; Cvach, Maria; Lavezza, Annette; Friedman, Michael; Bhatia, Elys; Brotman, Daniel J.; Hoyer, Erik H.
Abstract: Aim: Characterize the relationship between patient ambulatory status and in‐hospital call bell use. Background: Although call bells are frequently used by patients to request help, the relationship between physical functioning and call bell use has not been evaluated. Methods: Retrospective cohort study of 944 neuroscience patients hospitalized in a large academic urban medical centre between April 1, 2014 and August 1, 2014. We conducted multiple linear regression analyses with number of daily call bells from each patient as the primary outcome and patients' average ambulation status as the primary exposure variable. Results: The mean number of daily call bell requests for all patients was 6.9 (6.1), for ambulatory patients 5.6 (4.8), and for non‐ambulatory patients, it was 7.7 (6.6). Compared with non‐ambulatory patients, ambulatory patients had a mean reduction in call bell use by 1.7 (95% CI 2.5 to −0.93, p < .001) calls per day. In a post hoc analysis, patients who could walk >250 feet had 5 fewer daily call bells than patients who were able to perform in‐bed mobility. Conclusion: Ambulatory patients use their call bells less frequently than non‐ambulatory patients. Implications for Nursing Management: Frequent use of call bells by non‐ambulatory patients can place additional demands on nursing staff; patient mobility status should be considered in nurse workload/patient assignment.